Rising trend of proximal femoral nail in therapy of Extracapsular Hip Fractures - Ajit Ganvir; Deependra Sonkar; Jiten Shukla; Sanjeev Gaur (International Journal of Medical Research and Review, 2015)
Introduction: Fracture distal to the capsular attachment i.e. pertrochanteric area of hip including intertrochanteric and sub trochanteric region called as extracapsular hip fractures. Management of these fractures is big challenge in acute trauma. Unstable Extracapsular hip fractures accounts for 2% of all hip fractures. Dynamic hip screw (DHS) has some surgical drawback in unstable extra capsular hip fractures leading to more usage of proximal femoral nail (PFN).Aim of of Study: This study is undertaken to assess the changing patterns of Dynamic hip screw and Proximal femoral nail in extra capsular hip fractures.Materials and Methods: This is a retrospective study from 2008 to 2014. The study included 786 patients (Mean age 66.2 years) who underwent Dynamic hip screw and Proximal femoral nail fixation for extracapsular hip fractures. Out of 786 patients, 508 patients had DHS fixation and 278 patients had PFN fixation.Results: This study evaluated early complications and technical failures of both methods. Fracture classification used was AO type and patients were divided into two methods of fixation. Data analysis showed dramatically rising trend of PFN.Conclusion: We have concluded that PFN was used aggressively in the last 3 years which may be due to the changing behavior of fracture pattern. It may be intrinsic attraction to new surgical techniques with the younger orthopaedic surgeons.